Revolutionizing Solar Cell Efficiency: Unleashing Radio waves for Unprecedented Energy Conversion from Signals to Watts - George Edison (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The development of solar cells has made significant strides thanks to the search for effective and sustainable energy sources. This paper explores the ground-breaking idea of radio wave-integrated solar cells, a cutting-edge strategy that makes use of the interaction between radio waves and solar cells to improve energy conversion efficiency. The theoretical underpinnings, experimental approaches, case studies, prospective applications, difficulties, and future prospects in radio wave-driven energy conversion are all thoroughly explored in this article. The article begins by describing the underlying issues with current solar cell technology, highlighting the significance of boosting efficiency and taking a bigger picture approach to sustainability. The use of radio waves in solar cells is then covered in detail, along with the principles that enable improved energy conversion. Radio wave-integrated solar cells present a novel approach for enhancing the spectral sensitivity and energy production of the solar cell via radio wave-induced resonances and synergistic energy capture. Numerous case studies demonstrate the usefulness and effects of radio wave-integrated solar cells in various contexts. These case studies highlight the adaptability and revolutionary potential of this technology, which ranges from urban energy harvesting to powering wearable and enabling communication networks. The paper also discusses the effects of radio wave-driven energy conversion on decentralization, IoT device power, and applications for space-based solar power on global energy sustainability goals. Despite the potential of radio wave-integrated solar cells, difficulties still exist. The main challenges of efficiency optimization, material choice, environmental variability, integration, energy storage, standards, regulation, and economic viability are described in the article. Each difficulty provides a chance for creativity and teamwork to advance technology. Future developments in solar cells with radio wave integration will use a multidisciplinary approach. Radio wave-absorbing materials will need to be improved, and advances in materials science, nanotechnology, and electromagnetic engineering will be essential. While partnerships with governments and international organizations will encourage integration and acceptance, collaborative efforts between researchers, politicians, and companies will set standards and rules. This review paper highlights how radio wave-integrated solar cells have the potential to revolutionize energy conversion efficiency and sustainability. This article contributes to a thorough understanding of radio wave-driven energy conversion, paving the way for a more effective and sustainable energy future by clarifying the theoretical underpinnings, showcasing successful case studies, and addressing difficulties and future directions.